Schematic Entrance Process and Site Zoning Cultural Arts Center in Jembrana, Bali - Saraswati, Ni Komang Puja Astiti Adra; Trimarianto, Ciptadi; Mudra, I Ketut (Journal of A Sustainable Global South; Vol 2 No 2 (2018): August 2018DO - 10.24843/jsgs.2018.v02.i02.p07, 2018)
Art is one of cultural elements that has an aesthetic value, and is carried out by a group from people hereditary. Cultur-al arts of a region can be developed to gain any profits in tourism sector as well as sustainable.  Therefore, Jembrana Regency which has a unique cultural art attempts to improve their tourism sector, as well as  sustainable and the publi-cation of its culture by establishing Cultural Arts Centre. Cultural Arts Centre in Jembrana is an area of buildings com-plex with an open stage as a performance area, exhibition building, restaurant, and cafeteria. In their planning process, it falls into initial stage, programming process and schematic process with site and building design criteria. The sche-matic process consists of two parts, site and building design schematic. Site design schematic is a process to deter-mine the site entrance and zonation that refer to the design criteria for the site entrance and zoning that have been de-termined. Thus, the placement of entrance as well as each building within the site is in accordance to its function de-mands. Index Terms — arts, cultural arts, jembrana.